Diabetes Mellitus Patients' Knowledge About Hypoglycemia and Initial Management of Hypoglycemia - Abiddin, Andi Hayyun; Anam, Agus Khoirul; Mercado, Myrna; Amalia, Dewi Riska (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2023)
Acute complications Diabetes Mellitus such as hypoglycemia is an emergency situation that can occur in the course of Diabetes mellitus disease. Hypoglycemia is a result of lower blood sugar levels below normal. The purpose of this research is to know the description of Diabetes Mellitus patient's knowledge about Hypoglycemia and the initial treatment of Hypoglycemia. The research design used descriptive research design and purposive sampling technique with a sample size of 30 people. Data collection using questionnaire sheet. The results showed that Diabetes Mellitus patients on the initial handling of Hypoglycemia found that 46.7% were in the category of knowledge enough and 16.7% less. Counseling by Polyclinic officers in Diabetes Mellitus patients about early handling Hypoglycemia needs to be done to treat Hypoglycemia.